3-Monochloropropane-1, 2-diol causes spermatogenesis failure in male rats via Sertoli cell dysfunction but not testosterone reduction. (1st May 2022) - Xing, Hanzhu; Chen, Shanbin; Wang, Xiaoli; Li, Jinwang; Ren, Fazheng
Graphical abstract: Highlights: Mechanism of toxicity of 3-MCPD was studied in vivo and in primary testicular cells. 3-MCPD causes severe spermatogenesis failure in male rats. Serum but not inter-testicular testosterone declines in 3-MCPD-exposed rats. Meiosis arrest after 3-MCPD exposure but spermatogonial stem cell keeps self-renewal. 3-MCPD inhibits AR signalling and expression of paracrine factors in Sertoli cells. Abstract: 3-Monochloropane-1, 2-diol (3-MCPD), a common food contaminant, has been confirmed to impair male fertility, but the mechanism has not been fully clarified. This study systematically explored the spermatogenesis impairment induced by 3-MCPD in vivo and in vitro with a focus on Sertoli cells (SCs) and spermatogonial stem cells (SSCs). After adult male Sprague–Dawley rats were administered 36 and 72 mg/kg b.w./day 3-MCPD daily for 4 weeks, the total sperm concentration dramatically decreased by 28.9 % and 57.7 %, respectively, and obvious testicular seminiferous tubule atrophy was observed. 3-MPCD exposure decreased serum testosterone levels but not intratesticular testosterone levels and upregulated the expression of steroidogenesis enzymes in both rat testes and primary Leydig cells. 3-MCPD did not reduce the number and self-renewal marker PLZF + of SSCs; however, it downregulated the key meiotic genes Stra8 and Rec8 in the rat testis but not in primary germ cells. Although SC counts were not affected, 3-MCPD downregulated androgen receptor (AR) in rat testes and primary SCs. In addition, 3-MCPD downregulated p-CREB (transcription factor of AR), paracrine meiosis regulators Nrg1 and Nrg3 and retinoic acid synthetase Aldh1a1 in primary SCs. In summary, 3-MCPD caused impairment of spermatogenesis by inhibiting secretion of meiosis regulators and disturbing testosterone signalling in SCs.